Education Beyond AI: Building Integrity Through Authentic Assessment - Wahidin; Soelistiono, Soegianto; Tanjung, Rona (Global Writing Academica Researching & Publishing, 2025)
The advancement of artificial intelligence (AI) has transformed the paradigm of higher education assessment, challenging the effectiveness of traditional examination methods such as essays and multiple-choice tests. AI technologies, like ChatGPT, enable students to generate high-quality responses rapidly, triggering an authenticity crisis in academic assessments. Research indicates that 56% of global students, including those in Indonesia, use AI for assignments or exams, with 54% considering it a form of cheating (BestColleges, 2023). This paper aims to analyze the weaknesses of traditional exams in the AI era and propose authentic evaluation approaches through a conceptual discussion based on the analysis of challenges and new strategies. Key findings include recommendations for project-based exams, assessments of learning processes, hands-on practical exams, and the integration of AI literacy and ethics into the curriculum. This transformation demands that lecturers serve as facilitators and authentic evaluators while developing curricula focused on competence, creativity, and soft skills. Consequently, higher education can produce graduates who are not only academically proficient but also critical, creative, and responsible in leveraging AI.